Invertebrate zoology a tree of life approach - Schierwater, B. (Bernd) 1958-; DeSalle, Rob (CRC Press, an imprint of the Taylor & Francis Group, 2022)
"This book presents a comprehensive overview of invertebrate organismal zoology (IZ), defining invertebrates as any multicellular organism without a backbone (excluding plants and Fungi). While there are many IZ textbooks on the market, few combine the classical anatomical information with the newer genome level DNA sequence data and evo-devo data for teaching purposes. This book documents the latest research in these areas and combines it with classical information, giving students a unique opportunity to learn the biology of these organisms."--Provided by publisher.